2019
DOI: 10.1016/j.ejmg.2018.12.004
|View full text |Cite
|
Sign up to set email alerts
|

Effective communication in the era of precision medicine: A pilot intervention with low health literacy patients to improve genetic counseling communication

Abstract: Effective communication, where all parties share a common understanding, is necessary to realize the promise of Genomic Medicine. It is especially salient given the imperative to increase the participation of diverse populations in genomics research and to expand the reach of clinical genomics. We have previously shown that cancer genetic counseling is suboptimal for patients with limited health literacy. To address this finding, we implemented a pilot study to improve verbal communication between genetic coun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
48
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 46 publications
(49 citation statements)
references
References 55 publications
0
48
0
1
Order By: Relevance
“…Low health literacy results in excessive risky behaviour and poor health outcomes, including poor health awareness, an increased incidence of non-communicable diseases (NCDs), poor labelling of intermediate diseases and the inadequate use of preventive measures in health services [1,10−13] . As such, improving health literacy has evolved as a public health goal, and many countries have taken measures to improve the level of health literacy of their citizens [14,15] .…”
Section: Resultsmentioning
confidence: 99%
“…Low health literacy results in excessive risky behaviour and poor health outcomes, including poor health awareness, an increased incidence of non-communicable diseases (NCDs), poor labelling of intermediate diseases and the inadequate use of preventive measures in health services [1,10−13] . As such, improving health literacy has evolved as a public health goal, and many countries have taken measures to improve the level of health literacy of their citizens [14,15] .…”
Section: Resultsmentioning
confidence: 99%
“…Suggesting that patients bring another adult for support if they feel comfortable doing so is also likely to improve patient satisfaction following the appointment, particularly if it is indicated that the nature of the information that will be discussed could be new, complex and overwhelming, and that having a 'second pair of ears' is something many patients nd useful. Normalising these responses to genetic information and appointments is likely to empower patients to ask more questions and seek alternative sources of information as suggested by the clinician (14), rather than turning to Dr Google.…”
Section: Discussionmentioning
confidence: 99%
“…Joseph and Lee et al (14) assert that 'access alone is not su cient to ensure quality of care and equity in genomic medicine'. While this is important in every area of healthcare, it is particularly true of clinical genetics, where health literacy can be especially challenging (15).…”
Section: Introductionmentioning
confidence: 99%
“…(2018) yılında yaptıkları çalışmada danışmanlar tarafından geliştirilen iletişim teknikleri ve stratejileri hasta çıktılarını olumlu etkilemekte olduğu sonucuna varmışlardır. 56 Lyndon ve ark. (2011) yılında, Park ve ark.…”
Section: Discussionunclassified